Mapping Complex Systems: Responses to Intimate Partner Violence Against Women in Three Refugee Camps - Horn, Rebecca; Wachter, Karin; Friis-Healy, Elsa A.; Ngugi, Sophia Wanjku; Creighton, Joanne; Puffer, Eve S. (Frontiers in Human Dynamics, 2021)
Armed conflict and forced migration are associated with an increase in intimate partner violence (IPV) against women. Yet as risks of IPV intensify, familiar options for seeking help dissipate as families and communities disperse and seek refuge in a foreign country. The reconfiguration of family and community systems, coupled with the presence of local and international humanitarian actors, introduces significant changes to IPV response pathways. Drawing from intensive fieldwork, this article examines response options available to women seeking help for IPV in refugee camps against the backdrop of efforts to localise humanitarian assistance. This study employed a qualitative approach to study responses to IPV in three refugee camps: Ajuong Thok (South Sudan), Dadaab (Kenya), and Domiz (Iraqi Kurdistan). In each location, data collection activities were conducted with women survivors of IPV, members of the general refugee community, refugee leaders, and service providers. The sample included 284 individuals. Employing visual mapping techniques, analysis of data from these varied sources described help seeking and response pathways in the three camps, and the ways in which women engaged with various systems. The analysis revealed distinct pathways for seeking help in the camps, with several similarities across contexts. Women in all three locations often “persevered” in an abusive partnership for extended periods before seeking help. When women did seek help, it was predominantly with family members initially, and then community-based mechanisms. Across camps, participants typically viewed engaging formal IPV responses as a last resort. Differences between camp settings highlighted the importance of understanding complex informal systems, and the availability of organisational responses, which influenced the sequence and speed with which formal systems were engaged. The findings indicate that key factors in bridging formal and community-based systems in responding to IPV in refugee camps include listening to women and understanding their priorities, recognising the importance of women in camps maintaining life-sustaining connections with their families and communities, engaging communities in transformative change, and shifting power and resources to local women-led organisations.